Replication ethics. - Kent, Adrian (Futures, 2019)
Highlights • The effective emulation of humans in software is a speculative but not implausible future technology. • Decisions about whether to replicate the same human many times, or many humans once, are not straightforward. They require a view on whether diversity of replication is intrinsically valuable. • These questions provide a clean and intriguing thought experiment that illuminates a previously unconsidered aspect of population ethics, which is also relevant for more immediate ethical and policy questions. Abstract Suppose some future technology enables the same consciously experienced human life to be repeated, identically or nearly so, N times, in series or in parallel. Is this roughly N times as valuable as enabling the same life once, because each life has value and values are additive? Or is it of roughly equal value as enabling the life once, because only one life is enabled, albeit in a physically unusual way? Does it matter whether the lives are contemporaneous or successive? We argue that these questions highlight a hitherto neglected facet of population ethics that may become relevant in the not necessarily far distant future.